Tourette Syndrome: A General Pediatrician's 35-Year Experience at a Single Center With Follow-up in Adulthood. (February 2015) - Byler, Debra L.; Chan, Lisa; Lehman, Erik; Brown, Ashley D.; Ahmad, Syeda; Berlin, Cheston
A retrospective analysis of a 35-year single-center experience with pediatric tics and Tourette syndrome was conducted. 482 charts from 1972 to 2007 were reviewed. Follow-up surveys were mailed to last known address and 83 patients responded (17%). Response rate was affected by long interval from last visit; contact information was often incorrect as it was the address of the patient as a child. Males constituted 84%. Mean tic onset was 6.6 years. At first visit, 83% had multiple motor tics and >50% had comorbidities. 44% required only 1 visit and 90% less than 12 visits. Follow-up showed positive clinical and social outcomes in 73/83 survey responses. Of those indicating a poor outcome, mean educational level was lower and attention deficit/hyperactivity disorder and learning disabilities were significantly higher. Access to knowledgeable caregivers was a problem for adult patients. A shortage of specialists may in part be addressed by interested general pediatricians.